The Arbuscular Mycorrhiza and Phosphate Rock in Rehabilitation of Tin Tailings with Acacia Mangium and Peanut Agroforestry System - Satter, Md. Abdus (2000)
Malaysia has a vast area (200,000 ha) of abandoned barren sandy tailings unsuitable for agriculture and forestry. An attempt was made to convert these lands into a sustainable production system through establishment of Acacia mangium and peanut agroforestry system. The effect of arbuscular mycorrhiza (AM) in combination with P fertilization was studied on mangium seedlings in the glasshouse and on sole mangium and mangium + peanut agroforestry system on the sandy tailings in the field. Gafsa (GPR) and China (CPR) phosphate rocks along with TSP and control were tested with and without AM on mangium seedlings planted on the sandy tailings in the glasshouse. Growth, nodulation and nutrition of mycorrhizal seedlings were significantly higher than non mycorrhizal seedlings. Gafsa PR and TSP with AM produced superior seedlings compared to the other treatments probably due to higher P release from these two P sources. Mycorrhizal seedlings given GPR and TSP attained a height of 30 cm (recommended for outplanting) within 65 days compared to 85 days for non mycorrhiza I seedlings. The cheaper GPR with AM was hence recommended. I n another trial, six P rates (0, 20, 40, 60, 80 and 100 mg P kg-1 soil) in combination with two AM treatments were evaluated. Gafsa PR at 50 mg P kg-1 soil with AM was suggested for raising mangiu m seedlings on sandy tailings. Five rates of AM inoculum (0, 15, 30, 45 and 60 g plant-1) were then tested on peanut on the sandy tailings in the glasshouse. An inoculum level of 20 g planr1 was decided for field application. Field performance of AM inoculated and uninoculated mangium seedlings given 0, 50 and 100 g GPR planr1 were further evaluated in the sole culture for 160 days, and in association with peanut from 200 to 290 days after planting (DAP). Growth performance of inoculated and uninoculated mangium plants was similar until 70 DAP, but from 100 DAP onwards mycorrhizal plants had significantly higher growth with maximum growth obtained at 50 g GPR plant-1 . This combination is therefore recommended as optimum for mangium in the field. Yield of AM associated peanut grown at 185 to 285 DAP under mangium was significantly higher. This increased steadily from 1.18 to 1.63 t ha-1 with increase in GPR from 0 to 100 kg P ha- 1. Hence, 100 kg P ha-1 from GPR with AM has been suggested for the associated peanut. Organic matter and nutrient contents of the soil also improved under this agroforestry system, thus converting barren sandy tailings into a sustainable production system.